Similarity relationships and discriminatory value of the bibliometric indicators of the Scimago Journal and Country Rank. An analysis based on the generalist anthropology journals (2008-2017) - Traverso, Julieta V.; Ortiz-Jaureguizar, Edgardo; Miguel, Sandra; Posadas, Paula (Revista General de Información y Documentación, 2020)
Thirteen general anthropology journals, selected from the lists on the Scimago Journal and Country Rank portal, have been using a bibliometric methodology. The objectives were: a) to analyze the similarity relationships among the journals; b) to analyze the similarity relationships among the bibliometric indicators; c) to establish their discriminatory value. The indicators analyzed were those provided by the Scimago Journal and Country Rank portal. Univariate (Simpson proportions diagrams) and multivariate analysis techniques (phenogram and principal component analysis) were used. Among the conclusions of this study, it can be mentioned that: 1) five groups of journals are observed, which mainly responds to indicators of impact, prestige, and production; 2) the high correlation among some indicators (> 0.95), shows the existence of redundancy among them when grouping or discriminating the journals; 3) the groups of indicators found are not consistent with those based on the typology or the way of calculating the variables; and 4) an Editor/Director of a generalist anthropology journal has three strategies to increase the impact and prestige of him/her journal: a) that the "desirable" indicators have high values and the "undesirable" ones have low values; b) that the "desirable" indicators have high values, to compensate the adverse effect of high values in the "undesirable" indicators; 3) offset the relatively low values of the "desirable" indicators, with also low values of the "undesirable" ones.
Keywords: anthropology; scientific journals; bibliometrics; multivariate analysis; Scopus; Scimago Journal and Country rank